Region . dwutygodnik RKW NSZZ "Solidarność" Dolny Śląsk, no. 9, 1988 - [in cooperation with Ruch Społeczny "Solidarność", [ed. Mirosław Koźmian, Wratysław Nadodrzański, Michał Burmycha] (Koordynacja Wydawnicza przy RKW NSZZ "Solidarność" Dolny Śląsk, 1988)
Creation and circulation: From issue no. 56(1989) published legally